A new Hamiltonian formalism for singular Lagrangian theories - Duplij, S.A.; Дуплiй, С.А. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна. V.N. Karazin Kharkiv National University, 2011)
We introduce a version of the Hamiltonian formalism based on the Clairaut equation theory which allows us a self-consistent description of systems with degenerate (or singular) Lagrangian. A generalization of the Legendre transform to the case when the Hessian is zero is done using the mixed (envelope/general) solutions of the multidimensional Clairaut equation. The corresponding system of equations of motion is equivalent to the initial Lagrange equations, but contains “nondynamical” momenta and unresolved velocities. This system is reduced to the physical phase space and presented in the Hamiltonian form by introducing a new (non-Lie) bracket. Введена версия гамильтонова формализма, основанная на теории уравнения Клеро, которая позволяет самосогласовано описать системы с вырожденными (сингулярными) лагранжианами. Обобщение преобразований Лежандра на случай, когда гессиан равен нулю, выполняется с помощьюсмешанных (обертывающих/общих) решений многомерного уравнения Клеро. Соответствующая система уравнений движения эквивалентна первоначальным уравнениям Лагранжа, но содержит “нединамические” импульсы и неразрешенные скорости. Эта система сводится к физическому фазовому пространству и представлена в гамильтоновой форме с помощьювве дения новых (не-Ли) скобок. Введено версiюгамиль тонова формалiзму, заснована на теорiї рiвняння Клеро, яка дозволяє самоузгоджений опис теорiй з виродженими (сiнгулярними) лагранжианами. Узагальнення перетвореннь Лежандра на випадок, коли Гессiан дорiвнює нулю, виконується за допомогоюз мiшаних (обертуючих/загальних) рiшень багатовимiрного рiвняння Клеро. Вiдповiдна система рiвнянь руху еквiвалентна первiсним рiвнянням Лагранжа, але мiстить “недiнамiчнi” iмпульси та невирешинi швидкостi. Ця система зводиться до фiзичного фазавого простору i представлена в гамильтоновiй формi, вводячи новi (не-Лi) дужки.
Новий Гамiльтоновий формалiзм для сiнгулярних Лагранжевих теорiй
Keywords: Legendre transform; Hessian; multidimensional Clairaut equation; non-Lie algebra; Poisson brackets; перетворення Лежандра; Гессiан; багатовимiрне рiвняння Клеро; не-Лi алгебра; дужки Пуасона; преобразование Лежандра; Гессиан; многомерное уравнение Клеро; не-Ли алгебра; скобки Пуассона